Intervensi Edukasi dan Pemeriksaan Laboratorium untuk Meningkatkan Pengetahuan dan Deteksi Dini Penyalahgunaan NAPZA pada Pelajar - Dyah Eka Kurniawati; Chiilyatul Wafiroh; Ifadatin Haniah; Vicitra Prazjna Dyah Paramitha (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Substance abuse among adolescents remains a major public health concern because it affects physical health, mental well-being, academic performance, and social behavior. Limited knowledge regarding drugs, risk factors, and detection methods increases adolescents’ vulnerability to substance misuse. Educational interventions combined with laboratory practice can improve awareness and preventive behavior. Objective: This community service activity aimed to improve students’ knowledge and awareness regarding drug abuse (NAPZA), including its classification, causes, symptoms, and early detection through laboratory screening. Method: The activity was conducted by lecturers and laboratory staff in collaboration with a senior high school in Gresik, Indonesia. A total of 27 eleventh-grade students participated in the program, which included registration, pre-test assessment, educational sessions, interactive discussions, post-test evaluation, and urine screening using rapid test strips with AMP, MOP, and THC parameters. Knowledge improvement was measured by comparing pre-test and post-test scores. Result: The findings showed a significant increase in students’ knowledge after the intervention. The average score increased from 55.6 in the pre-test to 87.01 in the post-test. Twenty-two students participated in the laboratory screening, and all results were negative. Participants showed high enthusiasm during the practical session, which improved their understanding of drug detection methods and preventive awareness. Conclusion: Health education integrated with laboratory-based screening effectively improved adolescents’ knowledge and awareness regarding drug abuse prevention.